Inventory of Overburden in Alzheimer's Patient Family Caregivers with no Specialized Training - Pérez-Fuentes, María del Carmen (Int J Clin Health Psychol, 2017)
Background/Objective: Alzheimer-type dementia is one of the most frequent causes of dependence in an aging population, which combines with a considerable demand for care. Furthermore, when the caregiver is a family member or person without specialized training, such care impacts on that person's health. The Inventory of Overburden in Alzheimer's Patient Family Caregivers with no Specialized Training (IPSO-CA24) was designed to find out the needs of these caregivers and evaluate the caregiver's burden or distress. Method: The psychometric properties of the questionnaire were analyzed (in a reliability analysis, exploratory factor analysis and confirmatory analysis) based on the responses of 255 caregivers. Results: The factor analyses showed a six-factor structure (Reaction to diagnosis, Physical health, Psychological symptomatology (caretaker), Behavioral symptomatology (patient), Knowledge of the illness, and Level of dependence) explaining 66.52% of the total variance with a reliability of .75 to .93. Support was also found for its convergent validity. Conclusions: The IPSO-CA24 responds to the need for an instrument enabling multidimensional evaluation of the burden on the family caregiver without specialized training.